Numerical Simulation and Experimental Study on Gas Flow in an Open Lattice Structure for an Advanced Space Nuclear Power System - Wang, Zhipeng; Zhao, Jing; Ye, Zishen; Shi, Lei (Frontiers in Energy Research, 2022)
Helium flow in the rod bundle channel with an open lattice structure is an important phenomenon for the advanced gas-cooled nuclear core design. In this study, thermal analysis with helium flow in various channel designs is conducted based on CFD methods to determine a dimension-optimized rod bundle channel. An experimental study then follows in order to pick up an appropriate gas flow model in further numerical simulation. Finally, helium flow in the bundle channels consisting of 217 rods is simulated using this chosen flow model, which shows to satisfy the requirements of basic thermal analysis of a newly designed gas-cooled reactor with an open lattice structure. Generally, this work will contribute to the design and analysis of the future advanced space nuclear power system.